A clinical study of ectopic pregnancy at a tertiary care hospital of North Delhi - Sweta; Anjum, Shazia; Mendiratta, Suman Lata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: aim was to study the risk factors, clinical presentation and management of ectopic pregnancy in a tertiary care centre of North Delhi Methods: This was a prospective observational study conducted in the department of obstetrics and gynaecology Hindu Rao hospital and NDMC medical college, Delhi. A total of 65 cases of ectopic pregnancy were analyzed, over a period of 1 year that is from September 2020 to August 2021 Results: The incidence of ectopic pregnancy was 12.8/1000 deliveries. Majority of cases were multigravidas and of gestation age between 6 to 10 weeks. The common risk factors were PID, contraception failure (IUCD), tubal ligation, infertility, ART procedures, tubal surgery, and previous ectopic and previous abortion. Ultrasound, urine pregnancy test, serum β-hCG titre were done. Laparotomy was done in all cases. Surgery in form of salpingectomy, salpingo-oophorectomy, and uterine reconstruction was done. No maternal mortality occurred. Conclusions: Diagnosis of ectopic pregnancy requires clinical suspicion and supportive investigations like UPT, ultrasonography, β-HCG and laparoscopy. It is an important cause of admission to Hindu Rao hospital as maternal near miss cases.